Spatiotemporal simulation of blue-green space pattern evolution and carbon storage under different SSP-RCP scenarios in Wuhan - Guiyuan Li; Wangzhen Wang; Bowen Li; Zhongyuan Duan; Liang Hu; Jingwen Liu (Scientific Reports)
Abstract Rapid socioeconomic growth has altered land use patterns, resulting in a surge in worldwide CO2 emissions, triggering global climate challenges and adversely affecting human health, safety, and sustainable socioeconomic development. As a result, immediate action is required to undertake climate mitigation and adaptation strategies. This study, based on the causal logic of climate change, blue-green space patterns, and carbon emissions, uses the system dynamics (SD) model, patch-generating land use simulation (PLUS) model, and integrated valuation of ecosystem service and trade-offs (InVEST) models to simulate the evolution of blue-green space patterns and predict the spatial distribution of carbon storage in Wuhan to 2060 from 2030 under three SSP-RCP scenarios from CMIP6 and investigates their mechanisms. The findings show that across various SSP-RCP scenarios, the blue-green space patterns in Wuhan would decline over the next 30 years, with green spaces decreasing to some amount and blue spaces growing marginally. The carbon storage is also expected to decline due to the shrinking blue-green space patterns. The SSP126 scenario has the least shrinkage of blue-green spaces, resulting in a reduction of 7.18Tg in carbon storage. Under the SSP245 scenario, the expansion of non-blue-green spaces encroaches on blue-green spaces, resulting in an 8.13 Tg decrease in carbon storage. Across the SSP585 scenario, non-blue-green spaces expand the fastest, resulting in the highest loss of blue-green spaces and a considerable drop in carbon storage of 11.67 Tg. This research is extremely important for optimizing regional land use patterns, coordinating green and high-quality development in Wuhan, and assisting with the implementation of urban climate change adaptation plans.